Autologous Blood Injection and Wrist Immobilisation for Chronic Lateral Epicondylitis - Nicola Massy-Westropp; Stuart Simmonds; Suzanne Caragianis; Andrew Potter (Advances in Orthopedics)
Purpose. This study explored the effect of autologous blood injection (with ultrasound guidance) to the elbows of patients who had radiologically assessed degeneration of the origin of extensor carpi radialis brevis and failed cortisone injection/s to the lateral epicondylitis. Methods. This prospective longitudinal series involved preinjection assessment of pain, grip strength, and function, using the patient-rated tennis elbow evaluation. Patients were injected with blood from the contralateral limb and then wore a customised wrist support for five days, after which they commenced a stretching, strengthening, and massage programme with an occupational therapist. These patients were assessed after six months and then finally between 18 months and five years after injection, using the patient-rated tennis elbow evaluation. Results. Thirty-eight of 40 patients completed the study, showing significant improvement in pain; the worst pain decreased by two to five points out of a 10-point visual analogue for pain. Self-perceived function improved by 11–25 points out of 100. Women showed significant increase in grip, but men did not. Conclusions. Autologous blood injection improved pain and function in a worker’s compensation cohort of patients with chronic lateral epicondylitis, who had not had relief with cortisone injection.